Enhancing Student Learning Discipline: Evaluating the Effectiveness of Information Services through the Contextual and Learning (CTL) Model - Nadia Rista Yonanda; Dina Sukma (Universitas Ahmad Dahlan, 2023)
This research aims to improve student learning discipline with information services using a contextual teaching and learning (CTL) approach. This study used a quasi-experimental non-equivalent control group design. Sampling used a purposive sampling technique with 24 people in the experimental group and 24 people in the control group. The instrument used is a learning discipline questionnaire which has been validated by three experts in the field of Guidance and Counseling. Data from the study were analyzed using the Wilcoxon test. The results of research on student discipline show that before being given treatment, after treatment with 4 service sessions, the research results show that student learning discipline is in the high category. Data from research on learning discipline was obtained by Asymp. Sig. (2-tailed) 0.000. This shows that information services with a contextual teaching and learning (CTL) approach are effective in improving student learning discipline.